Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 6 - Logarithmic Functions - 6.1 Functions and Their Inverses - 6.1 Exercises: 38


$h^{-1}(x) = -\frac{x+10}{6}$

Work Step by Step

$h(x) = -6x-10$ Let $h(x) = y$: $y = -6x -10$ Switch the variables $x$ and $y$ to find the inverse and solve for $y$: $x = -6y -10$ $x + 10 = -6y$ $y = -\frac{x+10}{6}$ $h^{-1}(x) = -\frac{x+10}{6}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.